Red guards and political dissidents (II): Victims beyond a generation - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
Many former Red Guards who through the Cultural Revolution were encouraged to participate in unrestrained violence, saw the seamy side of the regime as a result and were themselves eventually suppressed and reached the conclusion that the system was corrupt and had to be changed. Former Red Guards who turned political activists varied greatly in their often vaguely defined outlooks and their intensity of commitment and activity. Wei Jingsheng, China’s most celebrated Red Guard-turned dissident, related a similar experience in an unfinished autobiographical account written before his arrest and smuggled out of the country in 1980. Many former Red Guards understandably see a silver lining in the destructive rampage they committed during the height of the Cultural Revolution. The Red Guard movement has come full circle. The human rights tragedy of the movement is threefold. In the first stage, the Red Guards were Mao’s “little generals” trampling on the human rights of their victims. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his